Pengaruh Dana Alokasi Khusus terhadap Indeks Pembangunan Manusia dengan Belanja Modal sebagai Variabel Mediasi - Muhammad Imam Nashshar; Budi Mulyana (Direktorat Jenderal Perbendaharaan, Kementerian Keuangan, 2022)
This research aims to understand the effect of the Special Allocation Fund (DAK) on the Human Development Index (IPM) with the government capital expenditure as a intervening variable. The sample in this research include 497 districts/cities of Indonesia during the period 2015 to 2019. The research method used in this research is the panel data regression with a fixed effect model (FEM) and path analysis. The results showed that: (1) DAK has a significant positive effect on government capital expenditure; (2) government capital expenditure has a significant positive effect on IPM; (3) DAK has a significant positive effect on IPM; and (4) DAK has a significant positive indirect effect on IPM through government capital expenditure.